A rapid coupling method for calculating the radiation field in decommissioning nuclear power plants. (15th June 2021) - Zhang, Zehuan; Song, Yingming; Ma, Shaohang; Guo, Yaping; Li, Chao
Highlights: Avoid the defect of calculating adjacent sources in the Point Kernel method. Provide a balanced choice between Monte Carlo and Point Kernel. It can be used with optimization methods to optimize decommissioning activities. Abstract: The decommissioning of nuclear facilities in nuclear power plants require a rapid dose estimated method. In the past, dose estimation methods include the deterministic and stochastic methods, which have some defects that polarize the computation overhead or accuracy. To address this, we proposed the Monte Carlo–point kernel (MC-PK) coupling method. This paper establishes a nuclear power plant model and uses the nuclear reactor's available power operation history to calculate device source data. For comparison, the radiation field has been calculated using both the Monte Carlo method and the MC-PK coupling method. The comparison result demonstrates that the MC-PK coupling method's calculation time is much less than that for the Monte Carlo method and the mean absolute percentage error of MC-PK relative to MCM is 24.92%. This study provides a viable strategy for the real-time radiation field calculation of decommissioning nuclear facilities.